Indicators of soil quality: a South-South development of a methdological guide for linking local and technical knowledge - Barrios, E.; Delve, Robert J.; Bekunda, Mateete A.; Mowo, J.; Agunda, J; Ramisch, Joshua J.; Trejo Tercero, M.T.; Thomas, Richard J. (2006)
The increasing attention paid to local soil knowledge results from a greater recognition that farmer knowledge can offer many insights into the sustainable management of tropical soils and that the integration of local and technical knowledge systems helps extension workers and scientists work more closely with farmers. A participatory approach and a methodological guide were developed to identify and classify local indicators of soil quality and relate them to technical soil parameters, and thus develop a common language between farmers, extension workers and scientists. This methodological guide was initially developed and used in Latin America and the Caribbean-LAC (Honduras, Nicaragua, Colombia, Peru, Venezuela, Dominican Republic), and was later improved during adaptation and use in eastern African (Uganda, Tanzania, Kenya, Ethiopia) through a South–South exchange of expertise and experiences. The aim of the methodological guide is to constitute an initial step in the empowerment of local communities to develop a local soil quality monitoring and decision-making system for better management of soil resources. This approach uses consensus building to develop practical solutions to soil management constraints identified, as well as to monitor the impact of management strategies implemented to address these constraints. The particular focus on local and technical indicators of agroecosystem change is useful for providing farmers with early warnings about unobservable changes in soil properties before they lead to more serious and visible forms of soil degradation. The methodological approach presented here constitutes one tool to incorporate local demands and perceptions of soil management constraints as an essential input to relevant research for development activities. The participatory process followed was effective in facilitating farmer consensus; for example, about which soil related constraints were most important and what potential soil management options could be used. Development of local capacities for consensus building constitute a critical step prior to collective action by farming communities resulting in the adoption of integrated soil fertility management strategies at the farm and landscape scale.